COMPARISON OF FACTORS AFFECTING THE LEVEL OF FRAUD IN LQ-45 INDEX CORPORATE FINANCIAL REPORTS - Muhamad Hayan Amsaroka (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This research intends to identify the possibility what companies listed on LQ 45 Index will commit the fraudulent financial statement after the Covid-19 pandemic. In addition, the research aims to assign the most influential account will commit in fraudulent financial statement. In this research, Companies listed on the LQ 45 Index in 2020 and 2021 were selected be the sample for this research, and financial reporting from 2020 and 2021 was collected. Using the Beinish Model M-Score, sample was divided into two groups, namely manipulators and non-manipulators. Furthermore, to find the most influential variables, a Mann Whitney test was carried out by using the SPSS. The result indicates that in 2020 and 2021, respectively, around 10% and 17% of registered companies are suspected of committing fraud. This study also reveals accounts in financial statements such as revenue, sales, profit, and cash flow to be very important key accounts that need to be considered in assessing financial statements because the information contained a significant possibility to be manipulated.